MODIFIKASI PATI SAGU DENGAN METODE HEAT MOISTURE TREATMENT - La Ega; Cynthia Gracia Christina Lopulalan (Universitas Pattimura, 2015)
This objective of the research was to obtain HMT sago starch having the physical characteristics that can be applied as raw materials in food processing. A completely randomized experimental design with heating temperature as the treatment was applied. Three levels of treatments were assigned, i.e: heating temperature of 90ºC, 95ºC, and 100ºC. Results were analyzed statistically using analysis of variance and Tukey test. Results showed that HMT modified sago starch by heating process at 100ºC had good stability having lower viscosity and moisture content, similar pH, and the degree of whiteness of 71.91%, as well as gel strength of 94.17%.